How are Muslims Interested in Using Sharia Insurance? Empirical Study of Karanganyar Community in Indonesia - Jannah, Fadzkhul; Sukardi, Budi (Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: Indonesia is a densely populated country where most of the population is Muslim. These conditions, such as Sharia insurance, can be an excellent opportunity for the Sharia sector. However, in general, the development of the sharia sector is not as significant as the development of conventional finance. Research Methods: This study is quantitative. Used in this research is the descriptive quantitative method. The number of samples in this study was 83 respondents. Respondents in this study were the Muslim community of Karanganyar. The sampling technique used is probability sampling, namely, giving questionnaires to respondents. The tests used to prove and analyse the data are validity, reliability, classical assumption, model determination, multiple linear regression, F-test, and t-test. Results: This study approves that religiosity, knowledge, income, and promotion positively affect the Muslim community's interest in using Sharia insurance in Karanganyar community, Central Java, Indonesia. Conclusion: Religiosity and promotion positively and significantly affect the Muslim community's interest in using Sharia insurance. Knowledge and income do not positively affect the Muslim community's interest in using Sharia insurance.